2018
DOI: 10.3847/1538-4357/aac018
|View full text |Cite
|
Sign up to set email alerts
|

The Circumstellar Disk and Asymmetric Outflow of the EX Lup Outburst System

Abstract: We present Atacama Large Millimeter/submillimeter Array (ALMA) observations at 0.3 -resolution of EX Lup, the prototype of the EXor class of outbursting pre-main sequence stars. The circumstellar disk of EX Lup is resolved for the first time in 1.3 mm continuum emission and in the J=2-1 spectral line of three isotopologues of CO. At the spatial resolution and sensitivity achieved, the compact dust continuum disk shows no indications of clumps, fragments, or asymmetries above 5-sigma level. Radiative transfer m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
49
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(57 citation statements)
references
References 81 publications
(132 reference statements)
7
49
1
Order By: Relevance
“…We note that several disks in Lupus 3 show systemic velocities in that range (e.g. EX Lup at +4.4 km/s Hales et al 2018 or the sources in Ansdell et al 2018). The rest of the ALMA sources were not detected in CO and have an upper limit to their CO(2-1) fluxes of ∼6 mJy/beam (1 σ) in a 0.3 km/s channel.…”
Section: Alma: Gas Emission Detectionsmentioning
confidence: 74%
“…We note that several disks in Lupus 3 show systemic velocities in that range (e.g. EX Lup at +4.4 km/s Hales et al 2018 or the sources in Ansdell et al 2018). The rest of the ALMA sources were not detected in CO and have an upper limit to their CO(2-1) fluxes of ∼6 mJy/beam (1 σ) in a 0.3 km/s channel.…”
Section: Alma: Gas Emission Detectionsmentioning
confidence: 74%
“…Paβ in the quiescent spectra might still trace accretion, as also found by Sipos et al (2009), but orders of magnitude lower than in the outburst phase. Hales et al (2018) reported the first spatially resolved observation of the disk around EX Lup, obtained with ALMA at 0.3 resolution in 1.3 mm continuum emission and in the J = 2-1 spectral line of 12 CO, 13 CO, and C 18 O. The compact dust continuum disk does not show indication of clumps or asymmetries in their data and is consistent with a characteristic radius of ∼23 au.…”
Section: Outburst Vs Post-outburst Phase In the Near-irmentioning
confidence: 67%
“…In Fig. 5, the top panel, we show the radial brightness profile after de-projecting the detected feature, using a position angle of 333 • , as determined through the azimuthal profile (bottom panel of the same figure), and an inclination of 38 • (Hales et al 2018). The feature peaks at around 60 au, with a sharp inner edge at ∼34 au and a shallower outer edge at ∼88 au.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations